Protective Effects of Selenium against Nickel Chloride-Induced Neprotoxicity in Preimplanted Rats - Ounassa Adjroud (e 6th Annual International Symposium on Environment, 16-19 May, 2011)
The environmental exposure to nickel may have a disastrous impact on human and animal public health. In this study we evaluated the protective effects of selenium against the nephrotoxic effects of NiCl2 in the preimplanted rats. NiCl2 was given on day 3 of pregnancy either as a single subcutaneous (sc) dose of 25, 50 or 100 mg/kg or in distilled drinking water at a dose of 20 mg/L/day for 16 consecutive days. Selenium was given as a sc injection (0.3 mg/kg) together with the higher dose (100 mg/kg) of NiCl2. Changes in plasma creatinine and urea were measured in treated and control groups on days 5 and 20 of gestation. The results showed that 100 mg / kg NiCl2 sc induced a significant increase in plasma creatinine on day 5 of gestation compared with controls. In contrast, on day 20 of gestation the NiCl2 induced a significant decrease in creatinine induced by doses of 25 and 50 mg / kg, whereas dose of 100 mg / kg increased plasma creatinine. Coadministration of selenium with NiCl2 significantly improved plasma creatinine on 5 and 20 days of gestation compared with NiCl2 administered alone. Moreover, on day 5 of gestation the NiCl2 increased significantly plasma concentrations of urea with the low and medium doses which became very significant with the highest dose. On day 20 of gestation, 50 mg / kg NiCl2 induced a significant decrease in plasma urea while the dose of 100 mg / kg induced an increase. Coadministration of selenium did not improve the concentrations of urea induced by NiCl2 alone. The NiCl2 administered in drinking water had no effect on plasma creatinine and urea. 3 doses of NiCl2 (sc) induced an alteration of renal architecture which is markedly improved by Selenium. The NiCl2 taken orally affects the medulla. These results suggested that selenium had no effect against nephrotoxicity induced by NiCl2 administered subcutaneously in pregnant rats.